2003
DOI: 10.1002/food.200390044
|View full text |Cite
|
Sign up to set email alerts
|

Using capillary isotachophoresis for the determination of biogenic amines and D‐isocitric acid in food products

Abstract: This paper presents results achieved in the determination of biogenic amines in various food products and quality evaluation of some commercial orange juices by capillary isotachophoresis. The highest amount of histamine was determined in frankfurters (146.75 mg x kg(-1)); the content of tyramine was either under detection limit of method or it was present in very low concentrations. The highest amount of cadaverine was determined in Karicka cheese (666.36 mg x kg(-1)). The limit of determination was 1.59 mg x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…This agrees with the report of Gaanappriya et al [24]. Karovicova and Kohajdona [25] reported that lactic acid fermentation can be suppressed by butyric bacteria activity in a slowly acidified medium. Moraru et al [14] reported that changes in the pH of the medium and lactic acid development are due to the production of organic acid by LAB culture.…”
Section: Acid Equivalent and Lactic Acid Production In The Stored Prosupporting
confidence: 93%
“…This agrees with the report of Gaanappriya et al [24]. Karovicova and Kohajdona [25] reported that lactic acid fermentation can be suppressed by butyric bacteria activity in a slowly acidified medium. Moraru et al [14] reported that changes in the pH of the medium and lactic acid development are due to the production of organic acid by LAB culture.…”
Section: Acid Equivalent and Lactic Acid Production In The Stored Prosupporting
confidence: 93%
“…The ratio of citric acid to D ‐isocitric acid is also one of the parameters that have been used to help establish a chemical profile for authentic fruit juices. Isocitric and citric acids in fruit juices have been analyzed by gas chromatography with flame ionization detector 4, HPLC 8, 9, CE with various separation modes 2, 5, 6, 10, 11. However, to our knowledge, the enantioseparation of DL ‐isocitric acid has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed that, the growth of Pediococcus pentosaceus LBF2 in soursop juice lead to pH reduction and increase in lactic acid. The main reason of this case has been attributed to the sugars consumption and production of organic acid by lactic acid cultures [30].…”
Section: Lactic Acid Production Ph and Total Soluble Solid (Tss) Of The Probioticated Soursop Juicementioning
confidence: 99%